RANCANG BANGUN JARINGAN SENSOR NIRKABEL UNTUK MEMONITOR PEMAKAIAN ENERGI LISTRIK PELANGGAN RUMAH TANGGA MENGGUNAKAN ARDUINO DAN ZIGBEE - , SHAGA SHAULAGARA; , I Wayan Mustika, S.T., M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this research, wireless sensor network is developed to monitor home energy consumption in real time. Wireless sensor network is built by utilizing voltage and current sensor which is controlled by Arduino Uno microcontroller and then it is connected with a wireless communication system using IEEE 802.15.4 protocol (Zigbee). The data collected fromthe nodes in a sensor network is a measurement of electrical energy consumption per household customers such as current and voltage and then for calculating rmsvalue of current and voltage, apparent power, real power, power factor and the last one is energy consumption. The readings from the sensors are transmitted wirelessly and then forwarded to the Coordinator to the PC and displayed on the screen to be remotely monitored periodically. This study focuses on the measurementof electrical energy. Electric provider such as PLN can utilize the wireless sensor networks to monitor electric energy usage per household customers so as to improve the time efficiency and performance while minimizing measurement error in terms of power recording manually by the customer. Customers can monitor the electric energy usage that has been consumed in real time which is displayed on the LCD 2x16.